Barriers and enablers faced by regional and rural schools in supporting student mental health: A mixed‐methods systematic review. (23rd October 2021) - Perkins, Alexandra; Clarke, Jessica; Smith, Ashlee; Oberklaid, Frank; Darling, Simone
Abstract: Background: Australian policy reports recommended schools to be leveraged to better support student mental health, with a focus on regional and rural areas where students have poorer mental health outcomes. In designing solutions to address this systemic gap, decision‐makers require an understanding of the barriers and facilitators experienced by regional and rural schools. However, current literature has focused on metropolitan schools and neglected to explore facilitators. Objective: To review the evidence on barriers and facilitators in delivering student mental health support experienced by regional and rural schools in Organisation for Economic Co‐operation and Development nations. Design: A mixed‐methods systematic review of peer‐reviewed and grey literature. Findings: The search identified 4819 studies. A full‐text review by 2 reviewers resulted in 5 papers, which met the inclusion criteria and were assessed using methodological appraisal. One study used qualitative data, 2 studies used quantitative data, and 2 studies were a mixed‐methods design. Discussion: While there was a paucity of studies, this review draws together the most up‐to‐date research. The barriers and facilitators were categorised into 3 themes: access to services and resources; mental health literacy of staff and parents; and communication and collaboration between stakeholders. Conclusion: This review presents a comprehensive synthesis of the literature and highlights opportunities to leverage rural and regional schools to support student mental health, focusing on the quality of communication and collaboration, and increasing access to services and resources, and mental health literacy. Research should explore the unique advantages of rural and regional areas to inform policy, including a focus on strengths.